2008
DOI: 10.4102/ojvr.v75i2.11
|View full text |Cite
|
Sign up to set email alerts
|

Acute and long-term effects of exposure to sodium monofluoroacetate (1080) in sheep

Abstract: Acute and long-term effects of a single, relative lyhigh oral dose (0.25a nd 0.30 mg/kg) of sodium monofluoroacetate (1080) on the survival and productivity of sheep were evaluated to establish a better understanding of 1080 poisoning and identify more specific changes diagnostic of toxicosis. In survivors, clinical signs of acute 1080 toxicosis such as salivation and lethar gywere generally very mild. Fasted animals were more prone to 1080 toxicity. In animals that died, more severe signs, including tachypnoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The decrease in body weight experienced in both the exposed male and female rats over 24 h (8.94% decrease in males and 6.74% decrease in females) is only expected to contribute to a small portion of the reduction in TV (Stahl, 1967), with the toxic effects of 1080 playing the major factor. The depression of respiratory function correlates with lung hemorrhage observed in both male and female rats administered 1080, which is in agreement with other reports of animals and humans with lung insults following 1080 intoxication (Brockmann, McDowell, & Leeds, 1955;Goh, Hodgson, Fearnside, Heller, & Malikides, 2005, Gooneratne et al, 2008, Harrisson et al, 1952Schultz, Coetzer, Kellerman, & Naudé, 1982).…”
Section: Discussionsupporting
confidence: 91%
“…The decrease in body weight experienced in both the exposed male and female rats over 24 h (8.94% decrease in males and 6.74% decrease in females) is only expected to contribute to a small portion of the reduction in TV (Stahl, 1967), with the toxic effects of 1080 playing the major factor. The depression of respiratory function correlates with lung hemorrhage observed in both male and female rats administered 1080, which is in agreement with other reports of animals and humans with lung insults following 1080 intoxication (Brockmann, McDowell, & Leeds, 1955;Goh, Hodgson, Fearnside, Heller, & Malikides, 2005, Gooneratne et al, 2008, Harrisson et al, 1952Schultz, Coetzer, Kellerman, & Naudé, 1982).…”
Section: Discussionsupporting
confidence: 91%
“…Sub-lethal doses of 1080 are metabolized and excreted by mammals within 8Á 24 h (e.g. rabbits, possums, sheep, goats, mice) with few, if any, long-term effects (Mead et al 1979;Eason et al 1994a;Gooneratne et al 1994Gooneratne et al , 2008. 1080 is not detected in their tissues after about 7 days (Eason et al1994b).…”
Section: Introductionmentioning
confidence: 97%
“…This study showed that although 1080 residues were quickly excreted in live mallards (Anas platyrhynchos), histopathological abnormalities sometimes occurred, particularly in heart and skeletal muscle tissue. Single dose studies on sheep (Ovis aries) also showed effects on heart, brain and lung tissue, but were without clinical significance (O'Connor et al 1999;Gooneratne et al 2008). Weka might also suffer tissue damage from a sublethal dose of 1080, although how this would affect their long-term health is unknown.…”
Section: Other Population Impactsmentioning
confidence: 99%